Early postnatal alterations in follicular stress response and survival in a mouse model of Classic Galactosemia - Synneva Hagen-Lillevik; Joshua Johnson; Kent Lai (BMC, 2022)
Abstract Primary ovarian insufficiency is characterized by accelerated loss of primordial follicles, which results in ovarian failure and concomitant menopause before age 40. About 1-3% of females in the general population are diagnosed with POI; however, greater than 80% of females with the inherited disease Classic Galactosemia will develop POI. Classic Galactosemia is caused by mutations in the GALT gene encoding the enzyme galactose-1 phosphate uridylyltransferase. While dietary restriction of galactose is lifesaving in the neonatal period, the development of complications including primary ovarian insufficiency is not mitigated. Additionally, the pattern(s) of follicle loss have not been completely characterized. The chronic accumulation of aberrant metabolites such as galactose-1-phosphate and galactitol are suspected culprits in the development of the sequelae, yet the mechanisms remain elusive. Our group uses a GalT gene-trapped mouse model to study the pathophysiology of primary ovarian insufficiency in Classic Galactosemia. We recently showed that differences in the Integrated Stress Response pathway occur in mutant ovaries that likely contribute to their primary ovarian insufficiency phenotype. Using immunofluorescent staining of histological sections of ovaries at progressive ages, we saw evidence of altered Integrated Stress Response activity in granulosa cells and primordial oocytes consistent with accelerated primordial follicle growth activation, aberrant DNA damage and/or repair, and increased cellular stress/death. Overall, our findings indicate that abnormal Integrated Stress Response in the Classic Galactosemia model ovary results in accelerated primordial follicle growth activation, sometimes referred to as "burnout." These aberrant early events help further clarify when/how the primary ovarian insufficiency phenotype arises under galactosemic conditions.